Symposium 7: Identities in Development - Courtney, Kathy; Deepwell, Frances; Turner, Andrew (Proceedings of the International Conference on Networked Learning, 2006)
This paper explores the implications for a team of educational developers who are now operating within a research environment when they have traditionally have placed greater emphasis on support within a collegiate culture. The context is a new capacity-building pedagogical research initiative within a UK higher education institution. This paper offers a preliminary analysis by attempting to map the research/development terrain to reveal synergies and dysfunctions that require attention if a community of inquiry is to flourish. We have used an action research approach in order to make sense of our own situation and provide a case study of our professional context. The implications are particularly evident in the online and email communities, where sharing data, permitting access and privacy are potential zones of conflict.